Towards Sustainable Manufacturing of Preterm Labor Treatment Drug Atosiban - Qvist,Thilda (2025)
Methods for synthesis of peptides using solid phase peptide synthesis (SPPS) are hampered by relying on large amounts of hazardous substances such as dimethylformamide (DMF) as solvent for peptide assembly and trifluoroacetic acid (TFA) a per/polyfluoroalkyl substance (PFAS) as reagent/solvent for side chain protecting group (PG) removal and peptide resin cleavage. Advances have been made towards replacing DMF as reaction solvent and TFA as cleavage reagent/solvent with limited number of attempts at combining both. The aim of the current work is to demonstrate that combining aqueous SPPS (ASPPS), utilizing conventional Fmoc-protected amino acids, with TFA /PFAS-free peptide resin cleavage is feasible for the manufacturing of the tocolytic peptide drug atosiban. By delaying preterm labor using atosiban fetal survival has been increased, without the drug showing any fetal adverse effects. This project looked at linker attachment to resin, SPPS in aqueous conditions and lastly TFA-free cleavage, resulting in a method that can serve as a basis for large-scale amenable, sustainable route to atosiban, from which a commercially viable process can be derived. Future work should look at improving efficiency of the proposed method, explore other reagents, examining the possibility of solvent recycling and addressing the economic perspective ensuring that the process is competitive with current manufacturing processes, affording a process that is sustainable from an economic, environmental and social perspective.
Keywords: SPPS; peptidesynthesis; atosiban; green chemistry